PENGARUH GREEN ACCOUNTING, KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI ISSI TAHUN 2019-2021 - Dea Agnes Efria; Mellya Embun Baining; Mohammad Orinaldi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Thesis entitled "The Influence of Green Accounting, Environmental Performance on Financial Performance in Mining Companies Registered at ISSI in 2019-2021". This is the result of a study that aims to determine the effect of Green Accounting, Financial Performance on Financial Performance in mining companies listed on the Indonesian Sharia Stock Index (ISSI) for 2019-2021. This research is a quantitative descriptive research. The data used is secondary data obtained from the annual reports of companies incorporated in the Indonesia Sharia Stock Index (ISSI) for 2019-2021. The sample of this study was obtained from purposive sampling technique, namely 13 companies with 3 years of research so that there were 39 observations. The data analysis technique used Multiple Regression Analysis. The results show that Green Accounting has no significant effect on the financial performance of mining companies listed on the Indonesian Sharia Stock Index (ISSI) for 2019-2021. Meanwhile, Environmental Performance has a significant effect on the Financial Performance of mining companies listed on the Indonesian Sharia Stock Index (ISSI) for 2019-2021. Green Accounting and environmental performance variables affect the financial performance of mining companies listed on the Indonesian Sharia Stock Index (ISSI) in 2019-2021.